An easily transfectable cell line that produces an infectious reporter virus for routine and robust quantitation of Kaposi’s sarcoma-associated herpesvirus reactivation - DeCotiis, Jennifer L. (J Virol Methods, 2017)
Reactivation of Kaposi’s sarcoma-associated herpesvirus (KHSV; also known as Human herpesvirus (HHV)-8) from latency is associated with progression to disease. The primary experimental models for studying KSHV reactivation are B lymphocyte cell lines derived from patients with primary effusion lymphoma (PEL). PEL models have remained essential tools for understanding molecular details of latency and reactivation, yet they have shortcomings. In particular, PEL cells are difficult to transfect with plasmid DNA, which limits their routine use in studies that require introduction of exogenous DNA. Moreover, PELs produce poorly infectious virus, which limits functional quantitation of the ultimate step in KSHV reactivation. In this study, we show that a recently published reporter virus system overcomes inherent difficulties of using PELs for studying viral reactivation. Vero rKSHV.294 cells harbor a recombinant reporter KSHV clone and produce infectious virus whose quantitation is strictly dependent on passage to naïve 293 cells. We show that the cells are easily transfectable, and produce significant amount of infectious virus in response to ectopically-expressed lytic switch protein Rta. In thus study, we derive optimal conditions to measure fold reactivation by varying experimental time periods and media volumes in infections and reporter enzyme reactions, and by eliminating background cellular and media activities. By measuring production of infectious virus, we demonstrate that Rta, but not the cellular transactivator Notch Intracellular Domain (NICD)-1, is sufficient to reactivate KSHV from latency. These data confirm previous studies that were limited to measuring viral gene expression in PELs as indicators of reactivation.